Modeling of the optimum level of financial provision of Ukrainian enterprises' innovative activities - N. Davidenko; H. Skrypnyk; Z. Titenko; O.V. Zhovnirenko (Global Journal of Environmental Science and Management)
The purpose of the article is the establishment of the tightness of the connection between the various sources of financing and the introduction of innovations at enterprises. In the process of research such scientific methods have been used: modeling – to determine the influence of the source of funding for innovation activities, on the number of new technological processes introduced and the introduction of new types of products; economic-statistical – to evaluate the dynamics of the amount of realized innovative products and the index of the efficiency of innovation costs; correlation-regression analysis – to determine the relationship density and the relationship between factors of influence and performance indicators; abstract-logical – for the implementation of theoretical and methodological generalizations. The results of the research – analyzed the connection of the indexes of dynamics of sources of financing of innovation activity and the amount of implemented new technological processes and development of new types of products for 2011-2017. The influence of the most significant sources of financing on the amount of innovations is described. Further development of methodological and practical aspects of the dependence of the amount of implemented innovative products and the index of the efficiency of innovation costs, using multiple regression models, has been found for the establishment of the influence of system-based economic indexes. The practical significance of the obtained results is to determine the optimal level of financial support for innovation activity of enterprises, which will allow predicting the growth of innovative processes in the country in the short and medium term.